Fabrication of chitosan@calcium alginate microspheres with porous core and compact shell, and application as a quick traumatic hemostat. (1st November 2020) - Wu, Xiaowei; Tang, Zonghao; Liao, Xiaoming; Wang, Zhengchao; Liu, Haiqing
Highlights: A hemostat has distinct core/shell structure, i.e. porous chitosan core and compact alginate shell. Interplay of porous chitosan core and Ca 2+ from alginate shell promotes blood clot formation. As hemostat, the core/shell microsphere is more efficient than porous chitosan microsphere. Abstract: A quick control of heavy hemorrhaging is critical to save the life of injured person. Herein we developed a hemostat of chitosan@calcium alginate microspheres through combination of microemulsion, polyelectrolyte complexation coating, and thermally induced phase separation. The alginate coated microspheres featured a structure of a porous chitosan core and a compact calcium alginate shell layer. Their in vitro and in vivo hemostatic properties were evaluated by the whole blood clotting kinetics, and rat tail amputation and liver laceration models. Compared to the porous chitosan microspheres, the alginate coated microspheres showed much enhanced hemostatic efficiency. The latter formed bigger blood clots; its hemostatic time on the liver laceration was substantially shortened to 53 ± 10 s from 107 ± 9 s of the former. It was shown that calcium ions released from the calcium alginate layer may accelerate the formation of blood clots. Such a biocompatible microsphere is a promising quick hemostat for controlling traumatic bleeding.